2016
DOI: 10.1074/jbc.m116.723551
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming Nurse-like Cells with Interferon γ to Interrupt Chronic Lymphocytic Leukemia Cell Survival

Abstract: Nurse like cells (NLCs) 3 are tumor-nurturing cells derived from CD14 ϩ monocytes in chronic lymphocytic leukemia (CLL) patients. In vitro studies have classified NLCs as CLLspecific, tumor-associated macrophage-like cells functioning as immune regulators and also possible inducers of emerging drug resistance (1-3). It has been shown recently that, in patients with diffuse large B cell lymphoma, a high density of CD68 ϩ /CD163 ϩ tumor-associated macrophages was significantly correlated with unfavorable progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Interestingly, the tumor supportive phenotype in MDC is reversible, as IFN-γ stimulation results in transdifferentiation of pro-tumorigenic (M2) CLL-associated monocytes towards M1 macrophages. 71 Similarly, inhibiting PD1 signals could restore macrophage function, 69 suggesting there is potential for therapeutic intervention in these pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the tumor supportive phenotype in MDC is reversible, as IFN-γ stimulation results in transdifferentiation of pro-tumorigenic (M2) CLL-associated monocytes towards M1 macrophages. 71 Similarly, inhibiting PD1 signals could restore macrophage function, 69 suggesting there is potential for therapeutic intervention in these pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Downregulation of CD31 expression by FcgR signaling initiated by therapeutic Abs may increase FcgR-mediated effector functions against cancer cells while simultaneously impairing cell-survival signals because of reduced interactions with CD38. Indeed, in a recent study, we demonstrated that downregulation of CD31 expression by IFN-g correlated with decreased chronic lymphocytic leukemia cell survival (39).…”
Section: Discussionmentioning
confidence: 76%
“…Another implication of targeting TAMs/NLCs is the potential to remove a major immunosuppressive stimulus from the tumour microenvironment. In particular, it has been noted that TAMs possess a PI3Kγ-dependent immune suppressor phenotype which is independent of an additional role in permitting immune checkpoint activity within the tumour microenvironment [19,68]. Recognition of these new roles of M2-like TAMs supports studies focusing on "driving" the macrophage phenotype towards a more "M1" phenotype [69,70] rather than ablating all macrophages [20,30,68].…”
Section: Tams/nlcs As a Therapeutic Targetmentioning
confidence: 97%
“…In particular, it has been noted that TAMs possess a PI3Kγ-dependent immune suppressor phenotype which is independent of an additional role in permitting immune checkpoint activity within the tumour microenvironment [19,68]. Recognition of these new roles of M2-like TAMs supports studies focusing on "driving" the macrophage phenotype towards a more "M1" phenotype [69,70] rather than ablating all macrophages [20,30,68]. For example, recent studies in models of pancreatic cancer and melanoma have shown that targeted inhibition of PI3Kγ by pharmacological inhibitors or genetic depletion of macrophage PI3Kγ promoted the conversion of M2-like TAMs to an M1-like phenotype [29,52,63].…”
Section: Tams/nlcs As a Therapeutic Targetmentioning
confidence: 99%